Resolution of Income Tax Case Regarding the Permanent Establishment of PT Bank Danamon Indonesia Tbk (Case Study of Supreme Court Decision No. 919/B/PK/DK/2015) - Irwan Haryowardani; Verry (CERED Indonesia Institute, 2023)
In 2011, a case involving PT Bank Danamon Indonesia, a private foreign company engaged in the banking and financial institution sector, occurred. Initially, the taxpayer (Director General of Taxation) issued a tax audit order (SP2) numbered Print-019/PJ.04/RIKSIS/2010 on July 16, 2010. The taxpayer (Directorate General of Taxation) issued a tax assessment letter for Article 26 Income Tax Article Number 00009/204/08/091/12 on February 7, 2012, for the tax period of September 2008, with an underpaid tax amounting to Rp 5,155,062,376,-. As a result, Bank Danamon Indonesia Tbk filed legal objections and appeals, including cassation to the Supreme Court. The resolution of the income tax case involving the permanent establishment of PT Bank Danamon Indonesia based on Supreme Court Decision No. 919/B/PK/PJK/2015 can be pursued through legal avenues, including objections, appeals, tax court lawsuits, and, as a last resort, cassation to the Supreme Court if the appeal decision in the tax court is rejected. The synchronization of the Supreme Court Decision No. 919/B/PK/PJK/2015 in terms of the implementation of Law Number 36 of 2008 on Income Tax leads to the Supreme Court granting the request for a review by the applicant for the review, and the respondent for the review (the Directorate General of Taxation) is declared the losing party. The tax court decision No. Put 54951/PP/M.XVA/13/2014 dated September 8, 2014, is hereby canceled.